2019
DOI: 10.3389/fmicb.2019.01420
|View full text |Cite
|
Sign up to set email alerts
|

P40 and P75 Are Singular Functional Muramidases Present in the Lactobacillus casei /paracasei/rhamnosus Taxon

Abstract: Lactobacillus casei and Lactobacillus rhamnosus proteins P40 and P75 belong to a large family of secreted cell wall proteins that contain a carboxy(C)-terminal CHAP or NlpC/P60 superfamily domains. In addition to their peptidoglycan hydrolases activity, proteins in this family are specific antigens of pathogens, frequently responsible of interactions with the host. L. rhamnosus GG and L. casei BL23 purified P40 and P75 proteins hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 43 publications
0
40
0
1
Order By: Relevance
“…Protein p40 and p75 were identified from many Lactobacilli species including L. casei, L. paracasei, and L. rhamnosus (145). They are secreted cell wall muramidases and have approximately molecular sizes of 40 and 75 kDa, respectively (74).…”
Section: Secreted Proteins and Peptides Protein P40 And P75mentioning
confidence: 99%
See 1 more Smart Citation
“…Protein p40 and p75 were identified from many Lactobacilli species including L. casei, L. paracasei, and L. rhamnosus (145). They are secreted cell wall muramidases and have approximately molecular sizes of 40 and 75 kDa, respectively (74).…”
Section: Secreted Proteins and Peptides Protein P40 And P75mentioning
confidence: 99%
“…The p40 transactivated the epidermal growth factor receptor (EGFR) in intestinal epithelial cells, inhibited apoptosis and preserved barrier function in the colon, thereby ameliorating intestinal injury and inflammation (17, 75, 76, 78, 109). Besides, p75 purified from L. rhamnosus GG and L. casei BL23 have anti-apoptotic activity by inducing the EGF/Akt pathway (145). Furthermore, the p40 and p75 proteins were able to protect the intestinal epithelial tight junctions and barrier functions by a protein kinase (PKC) and MAP kinase-dependent mechanism (76).…”
Section: Secreted Proteins and Peptides Protein P40 And P75mentioning
confidence: 99%
“…Lactobacillus casei BL23 (BL23) is a well-studied probiotic strain for which anti-inflammatory and anti-tumor effect have been described in mouse models 22 25 . Two secreted cell wall muramidases that contain a CHAP (NlpC/P60) domain have been characterized in BL23, P40 and P75, and homologs to these proteins are exclusively present in the L. casei taxon, that comprises mainly the species L. casei, L. paracasei and L. rhamnosus 26 . Their ability to stimulate growth and survival of epithelial cells was first described in L. rhamnosus GG 27 .…”
Section: Introductionmentioning
confidence: 99%
“…These proteins proved to have anti-apoptotic and anti-inflammatory effects mediated by the activation of the EGFR/Akt pathway. Then, it was shown that protein P40 reduces dextran sulfate sodium (DSS)-induced experimental colitis, and it induced mucin synthesis by intestinal epithelial cells (IEC), intestinal IgA production and promoted intestinal development in early life 26 , 28 31 . The abnormal cellular morphology of knock out mutants of L. casei and L. rhamnosus lacking these proteins showed that they are involved in the normal conformation of the bacterial cell wall; P75 is a γ-D-glutamyl-L-lysyl-endopeptidase required for daughter cell separation 28 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the lyophilized microbial biomass used to prepare a probiotic product contains the residual growth medium, which includes microbial metabolites produced and secreted/released by probiotic cells during growth. Such microbial products may include primary metabolites (e.g., lactate, acetate, propionate), bacteriocins, reuterin, or other secreted molecules (e.g., immunomodulatory secreted peptides; [43]), which can be defined as "postbiotics" [44]. The actual contribution of these molecules to the interaction of probiotic formulations on host health is not known but, in light of data obtained from in vitro experiments, cannot be excluded [45][46][47].…”
Section: Extracellular Microbial Products In Probiotic Formulationsmentioning
confidence: 99%